Wind Speed Influences on Marine Aerosol Optical Depth - Colin O'Dowd; Claire Scannell; Jane Mulcahy; S. Gerard Jennings (Advances in Meteorology)
The Mulcahy (Mulcahy et al., 2008) power-law parameterization, derived at the coastal Atlantic station Mace Head, between clean marine aerosol optical depth (AOD) and wind speed is compared to open ocean MODIS-derived AOD versus wind speed. The reported AOD versus wind speed (U) was a function of ∼U2. The open ocean MODIS-derived AOD at 550 nm and 860 nm wavelengths, while in good agreement with the general magnitude of the Mulcahy parameterization, follows a power-law with the exponent ranging from 0.72 to 2.47 for a wind speed range of 2–18 m s−1. For the four cases examined, some MODIS cases underestimated AOD while other cases overestimated AOD relative to the Mulcahy scheme. Overall, the results from MODIS support the general power-law relationship of Mulcahy, although some linear cases were also encountered in the MODIS dataset. Deviations also arise between MODIS and Mulcahy at higher wind speeds (>15 m s−1), where MODIS-derived AOD returns lower values as compared to Mulcahy. The results also support the suggestion than wind generated sea spray, under moderately high winds, can rival anthropogenic pollution plumes advecting out into marine environments with wind driven AOD contributing to AOD values approaching 0.3.